2016
DOI: 10.1074/jbc.m115.672287
|View full text |Cite
|
Sign up to set email alerts
|

Sar1 GTPase Activity Is Regulated by Membrane Curvature

Abstract: The majority of biosynthetic secretory proteins initiate their journey through the endomembrane system from specific subdomains of the endoplasmic reticulum. At these locations, coated transport carriers are generated, with the Sar1 GTPase playing a critical role in membrane bending, recruitment of coat components, and nascent vesicle formation. How these events are appropriately coordinated remains poorly understood. Here, we demonstrate that Sar1 acts as the curvature-sensing component of the COPII coat comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 50 publications
7
73
0
Order By: Relevance
“…Enhanced recruitment of SEC23 may be due to the formation of SAR1 dimers on the membrane (25)(26)(27). In fact, we found a significant amount of soluble SAR1 recruited to the membrane, although we were unable to distinguish soluble SAR1B from SAR1A as the two have the same SDS-PAGE mobility.…”
Section: Sar1b Binds Sec23 More Strongly Than Sar1amentioning
confidence: 56%
See 1 more Smart Citation
“…Enhanced recruitment of SEC23 may be due to the formation of SAR1 dimers on the membrane (25)(26)(27). In fact, we found a significant amount of soluble SAR1 recruited to the membrane, although we were unable to distinguish soluble SAR1B from SAR1A as the two have the same SDS-PAGE mobility.…”
Section: Sar1b Binds Sec23 More Strongly Than Sar1amentioning
confidence: 56%
“…It is easy to think of SAR1 as just a small part of a bigger COPII machinery, rather than focusing on the important roles SAR1 itself plays. Hannah et al (26) showed that the amphipathic helix of GTP-bound Sar1 stably penetrates the endoplasmic reticulum membrane, promoting local membrane deformation. As membrane bending increases, Sar1 membrane binding is elevated, ultimately culminating in GTP hydrolysis, which may destabilize the bilayer sufficiently to facilitate membrane fission.…”
Section: Sar1 As a Remodeler And Cargo Sizementioning
confidence: 99%
“…The first is based on the premise that Sar1 action is restricted to the ER, where it promotes membrane tubulation and ultimately accumulates at the neck of nascent COPII‐coated buds to facilitate bilayer scission upon GTP hydrolysis. This idea is supported by studies demonstrating the ability of recombinant Sar1 to create membrane tubules (Figure ), as well as more recent work demonstrating that Sar1 is capable of sensing membrane curvature . Additionally, the intrinsic GTPase activity of Sar1 is stimulated in the presence of elevated curvature, suggesting a mechanism by which it may drive transport carrier scission .…”
Section: Introductionmentioning
confidence: 68%
“…This idea is supported by studies demonstrating the ability of recombinant Sar1 to create membrane tubules (Figure ), as well as more recent work demonstrating that Sar1 is capable of sensing membrane curvature . Additionally, the intrinsic GTPase activity of Sar1 is stimulated in the presence of elevated curvature, suggesting a mechanism by which it may drive transport carrier scission . In a second model, Sar1 not only acts at the ER, but also on free transport carriers en route to the ERGIC.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation